232k views
4 votes
-3(x-1) + 8(x-3) = 6x + 7 - 5x

User Horyd
by
6.3k points

2 Answers

1 vote

Answer:

x=7

Explanation:

-3(x-1)+8(x-3)=6x+7-5x

-3x+3+8x-24=6x+7-5x

5x-21=x+7

4x=28

x=7

User Pawel Bieszczad
by
6.1k points
4 votes

Answer:

x=7

Explanation:

-3(x-1) + 8(x-3) = 6x + 7 - 5x

Distribute

-3x +3 +8x -24 = 6x +7 -5x

Combine like terms

5x -21 = x+7

Subtract x from each side

5x-x-21 = 7

4x -21 =7

Add 21 to each side

4x-21+21 = 7+21

4x = 28

4x/4 = 28/4

x=7

User FuzzyDuck
by
6.9k points